Outpatient Endocrine Protocol and Testing Coincides with Reduced Length of Postpituitary Surgery Admission - Eitan, Dana N.; Cave, Taylor B.; Bendok, Bernard R.; Krishna, Chandan; Lal, Devyani; Miglani, Amar; Patel, Naresh P.; Patra, Devi P.; Turkmani, Ali; Marino, Michael J. (Journal of Neurological Surgery Part B: Skull Base, 2024)
The study objective was to compare the length of stay (LOS) and the proportion of one-night admissions before and after the implementation of an endocrine monitoring protocol following endoscopic transsphenoidal surgery (ETSS) for pituitary adenoma.Patients who underwent transsphenoidal pituitary adenoma resection between July 1, 2018, and September 9, 2022, were identified, and divided into two cohorts before and after the implementation of the monitoring protocol. The overall LOS and number of nights of admission were recorded. Readmission within 30 days after surgery was also recorded. The number of outpatient laboratory tests performed and the time to the first test were also noted.Thirty patients were identified in the preprotocol group and 60 in the postprotocol group. The average admission length in the preprotocol group was significantly longer than the average admission length in the postprotocol group (2.4 vs. 1.7 days, p = 0.004). The percentage of one-night admissions increased from 13 to 57% (p < 0.001). There were no significant differences in readmission rates between the two groups (p = 0.681). The number of laboratory encounters increased from a mean of 1.38 to 2.40 (p = 0.030), while the time to the first test decreased from a mean of 3.43 to 2.36 days (p = 0.049).Patients admitted after ETSS for pituitary adenoma had shorter hospital stay and greater proportion of one-night admission with the implementation of an endocrine monitoring protocol. The all-cause readmission rate was not statistically different between the two groups. Through aggressive outpatient laboratory monitoring, one-night admission for ETSS may be feasible.
Keywords: pituitary adenoma; endoscopic surgery; postoperative stay; duration; readmission rate